Chitasil Edible Coating and Price Stability of Agricultural Commodities: An Islamic Economic Law Perspective - Nur Mifchan Solichin; Diah Nuraini; Aang Asari; Sukron Ma’mun (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
Agricultural commodity price instability in perishable markets is commonly explained as a supplyâ€“demand imbalance, yet such an interpretation overlooks the structural role of time constraints in market exchange. This study examines how post-harvest technology functions not only as a productivity tool but as an economic governance mechanism within the framework of Islamic economic law. Using an empirical legal method combined with juridicalâ€“sociological analysis, field interviews were conducted with horticultural farmers in Ngablak, Magelang, and interpreted through maqÄá¹£id asy-syarÄ«â€™ah and qawÄâ€˜id fiqhiyyah. The findings show that price volatility originates from forced-sale conditions caused by limited shelf life, where farmers sell under biological time pressure rather than economic choice. The application of Chitasil edible coating extends shelf life, enabling intertemporal selling and reducing the Price Stability Index from 1.37 (indicating high volatility) to approximately 0.6 (indicating moderate fluctuation). The mechanism stabilizes prices not by controlling prices directly but by redistributing temporal risk in market transactions. From the perspective of Islamic economic law, the technology eliminates the cause of value depreciation (rafâ€™ aá¸-á¸arar), protects economic value (á¸¥ifáº“ al-mÄl), and restores proportional riskâ€“benefit relations (al-gunmu bi al-gurmi). Furthermore, the technology functions as an institutional instrument of distributive justice by equalizing bargaining capacity without regulatory price intervention. This study concludes that post-harvest technology operates as a maqÄá¹£id-based economic governance mechanism: justice is achieved through structural market design rather than contractual restriction. The contribution lies in repositioning agricultural technology from a production tool into a normative instrument of distributive justice within Islamic economic law.